The Role of Information Technology in Improving the Efficiency and Effectiveness of Talent Management Processes - Derist Touriano; Sutrisno Sutrisno; Arlis Dewi Kuraesin; Sonny Santosa; Abu Muna Almaududi Ausat (Politeknik Ganesha Medan, 2023)
Amidst the current era of globalization and heightened business competition, organizations across diverse sectors encounter obstacles in the recruitment, cultivation, and retention of optimal talent. The strategic management of talent has emerged as a critical area of emphasis for organizations seeking to cultivate a skilled and proficient labor force. The present study aims to investigate the impact of information technology, specifically the implementation of a human resource management system, on enhancing the efficiency and effectiveness of talent management procedures. This research is qualitative in nature. The techniques used to obtain information involve careful observation and meticulous note-taking, followed by analytical procedures such as data reduction, visualisation, and inference. The results of this study show that the role of IT in improving the efficiency and effectiveness of talent management processes is significant. The use of IT in employee recruitment and selection, skills development, employee engagement, and data management provide many benefits to organisations. However, challenges such as data privacy and security, digital divide, organisational complexity, ethical aspects, and the importance of human interaction need to be addressed to achieve optimal results.